2017
DOI: 10.18203/2320-1770.ijrcog20170514
|View full text |Cite
|
Sign up to set email alerts
|

Changing trends in genital cancer

Abstract: Background: Globally, cancers in all forms are causing about 12% of all deaths. In developed countries cancer is the second leading cause of death accounting for 21% of mortality by other causes and in developing countries it ranks third, accounting for 9.5% of all deaths. The objective was to find the incidence of genital malignancy and any change in the trend at Pandit Jawahar Lal Nehru Memorial Medical College, Raipur, Chhattisgarh, India.Methods: This was a cross-sectional, retrospective, observational stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
0
2
1
Order By: Relevance
“…This may be due to higher order parity occurring at Nigeria when compared to our population where people are aware of the use of family planning methods. 7 Both ovarian and uterine cancer also commonly occurred in parous women in the present study, in contrary to the fact that parity gives protection to these cancers. This is similar to study results from Ghana.…”
Section: Discussioncontrasting
confidence: 84%
See 2 more Smart Citations
“…This may be due to higher order parity occurring at Nigeria when compared to our population where people are aware of the use of family planning methods. 7 Both ovarian and uterine cancer also commonly occurred in parous women in the present study, in contrary to the fact that parity gives protection to these cancers. This is similar to study results from Ghana.…”
Section: Discussioncontrasting
confidence: 84%
“…Cancer cervix was common among women with high parity (3-4). 2,7 But Nigerian studies showed that cancer cervix occurred at a higher order parity (5 and above). This may be due to higher order parity occurring at Nigeria when compared to our population where people are aware of the use of family planning methods.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation